Identify The Key Performance Indicators (KPI) for Badan Usaha Milik Desa (BUMDes) Raharja - Padmakusumah, Rizal R.; Zulganef; Brahmana, Sunardi S.; Nilasari, Irma; Handayani, Rini (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this study is to identify key performance indicators (KPI) in the type of village-owned enterprise (BUMDes) organization. This research is a case study research which is the result of Community Service activities (PKM) with the object of research being the Raharja Village Owned Enterprise (BUMDes Raharja). The research conducted is a qualitative research that aims to identify BUMDes Raharja using the latest version of the “key performance indicator” method developed by [1]. The results showed that BUMDes Raharja has been able to identify the type of KPI in the form of KPIs. However, BUMDes Raharja is still not sufficiently able to identify the types of KPIs in the form of KRIs, RIs, and PIs. Researchers suggest that BUMDes Raharja immediately identify KPIs immediately, because KPIs are the most important key indicators to control so that organizations can achieve success and avoid failure. The researcher also suggested that BUMDes Raharja also re-identify KRIs, RIs, PIs and KPIs so that the number of performance indicators each approaches the recommended 10/80/10 standard (parmenter, 2015).